Postactivation performance enhancement of amateur boxers` punch force and neuromuscular performance following 2 upper-body conditioning activities - Finlay, M. J.; Bridge, C. A.; Greig, M.; Page, R. M. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The purpose of this study was to assess the efficacy of upper-body punch-specific isometric (ISO) and elastic resistance (ER) conditioning activities (CAs) on the punch force and neuromuscular performance of amateur boxers.